Weight Status Modulated Brain Regional Homogeneity in Long-Term Male Smokers - Zhang, Mengzhe; Gao, Xinyu; Yang, Zhengui; Niu, Xiaoyu; Chen, Jingli; Wei, Yarui; Wang, Weijian; Han, Shaoqiang; Cheng, Jingliang; Zhang, Yong (Frontiers in Psychiatry, 2022)
Background: Tobacco smoking and overweight could lead to adverse health effects, which remain an important public health problem worldwide. Researches indicate that overlapping pathophysiology may contribute to tobacco addiction and overweight, but the neuro-biological interaction mechanism between the two factors is still unclear. Methods: The current study used a mixed sample design, including the following four groups: i) overweight long-term smokers (n = 24); ii) normal-weight smokers (n = 28); iii) overweight non-smokers (n = 19), and iv) normal-weight non-smokers (n = 28), a total of 89 male subjects. All subjects underwent resting-state functional magnetic resonance imaging (rs-fMRI). Regional homogeneity (ReHo) was used to compare internal cerebral activity among the four groups. Interaction effects between tobacco addiction and weight status on ReHo were detected using two-way analysis of variance, correcting for age, years of education and head motion. Results: A significant interaction effect between tobacco addiction and weight status is showed in right superior frontal gyrus. Correlation analyses show that the strengthen ReHo value in right superior frontal gyrus is positively associated with pack-year. Besides, main effect of tobacco addiction is specially observed in occipital lobe and cerebellum posterior lobe. As for main effect of weight status, right lentiform nucleus, left postcentral gyrus and brain regions involved in DMN are survived. Conclusions: These results shed light on an antagonistic interaction on brain regional homogeneity between tobacco addiction and weight status in right superior frontal gyrus, which maybe a clinical neuro-marker of comorbid tobacco addiction and overweight. Our findings may provide a potential target to develop effective treatments for the unique population of comorbid tobacco addiction and overweight.